Acoustic testing for phonologization - Shahin, Kimary (Canadian Acoustics, 2008)
The way shift arises from the acoustic signal, focusing on gradience in postvelar phenomena in Salish and Arabic, illustrating acoustic testing for phonologization, was studied. The phonologization occurs when categorical, non-numeric versions of numerically weighted phonetic constraints enter the strict dominance relations of the grammar. The phonetic properties are gradient but phonological properties are not. A key trigger for the shift between the phonetics and phonology is degree of gradience. The Salish words were produced by an adult male native speaker, and recording used a Marantz P420. The resonance in the area of F2 was measured for fricatives at the durational midpoints. Gradience was also examined and found to underlie phonologized patterns, and to indicate that certain patterns previously considered phonological, are perhaps phonetic.